Pengaruh Price, Product Quality, dan Brand Image terhadap Keputusan Pembelian iPhone: Studi Kasus Pengguna iPhone di Kota-Kota Besar - Tiara Salsabila Fasya; Maya Ariyanti; Yusza Reditya Murti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
People in Indonesia's major cities can't function without their cellphones in this digital era. Consumers are drawn to Apple's flagship product, the iPhone, due to its sophisticated technology, sleek design, and connected ecosystem. Pricing, product quality, and consumer perception of the brand are the three most important considerations when purchasing an iPhone. This study plans to apply a quantitative technique with a causal intent in a large Indonesian metropolis to evaluate the impact of these three variables on iPhone purchase decisions. We used a non-probability sampling technique to poll 155 respondents. On the obtained data, we performed Structural Equation Modeling Partial Least Square (SEM-PLS) analysis using the SmartPLS version 4.0 program. The results showed that consumers are impacted by price, product quality, and brand image when making purchases, both separately and in combination. The practical advice offered is that in order to boost satisfaction, trust, loyalty, and product attractiveness, organizations should prioritize competitive price, high product quality, and effective brand image management. In order to fully grasp how factors like pricing, product quality, and brand image interact with one another when consumers make purchases, this study theoretically stresses the importance of developing a more all-encompassing model. Using a wider range of methodologies, future studies can take into account more variables.